Carlos Hernández Sacristán, A phenomenological approach to syntax; the propositional frame. Universitat de Valencia-University of Minnesota, Valencia-Minnesota, 1990; 183 pp. - Vázquez Laslop, María Eugenia (El Colegio de México, 1994)
Se reseñó el libro: A phenomenological approach to syntax; the propositional frame.